Spontaneous regression of congenital epulis: a case report - Pedroso, Caique Mariano; Pomini, Marcos Cezar; Paz, Bianca; Dias, Gisele Fernandes; Alves, Fabiana Bucholdz Teixeira (Journal of Oral Diagnosis, 2020)
Congenital epulis (CE) is a rare benign tumor of the newborn (NB). The recommended treatment has been prompt surgical resection; however, spontaneous regression of the lesion is a more conservative management and should be considered in cases where lesions are not impairing neonatal deglutition and respiration efforts. The aim of this study is to describe the spontaneous regression of a CE in a NB. A one-day-old NB was referred to the hospital dentistry service with the reported presence of an alteration in the oral cavity associated with difficulty sucking during breastfeeding. During clinical evaluation, we observed a fibrous nodular lesion (0.80 x 0.80 cm), gum-like in color, on the right side of the NB’s jaw, with a pedicled aspect, and smooth surface. Initially, we proposed chan- ging the breastfeeding position and correctly oriented the mother on how to adapt the child to work with the clinical condition of the lesion. The probable diagnostic hypothesis was that of CE. It was suggested that the lesion be preserved and monitored during the NB’s hospital stay time and monthly until six months was reached, followed by quarterly monitoring until 15 months. During the clinical follow-up, significant reduction of the lesion was observed at three months (0.44 x 0.42 cm) and six months (0.20 x 0, 20 cm). After the six months follow up, further reduction of the lesion was not observed until tooth eruption. A longitudinal clinical follow-up was essential to certify the regression of the lesion, promoting the restoration of exclusive natural breastfeeding, avoiding unnecessary procedures, and contributing to the child’s quality of life.